2024
DOI: 10.1002/chem.202400019
|View full text |Cite
|
Sign up to set email alerts
|

Computational Study Into the Oxidative Ring‐Closure Mechanism During the Biosynthesis of Deoxypodophyllotoxin

Fintan G. Hardy,
Henrik P. H. Wong,
Sam P. de Visser

Abstract: The nonheme iron dioxygenase deoxypodophyllotoxin synthase performs an oxidative ring‐closure reaction as part of natural product synthesis in plants. How the enzyme enables the oxidative ring‐closure reaction of (‐)‐yatein and avoids substrate hydroxylation remains unknown. To gain insight into the reaction mechanism and understand the details of the pathways leading to products and byproducts we performed a comprehensive computational study. The work shows that substrate is bound tightly into the substrate b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
3

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 122 publications
2
4
3
Order By: Relevance
“…Our calculation showed that the hydrogen abstraction from the target C7′–H bond generates Fe III –OH and the substrate C7′-centered radical with a barrier of 15.5 kcal/mol. This barrier matches the one (14.0 kcal/mol) obtained from the cluster model calculations by de Visser et al…”
Section: Resultssupporting
confidence: 90%
See 4 more Smart Citations
“…Our calculation showed that the hydrogen abstraction from the target C7′–H bond generates Fe III –OH and the substrate C7′-centered radical with a barrier of 15.5 kcal/mol. This barrier matches the one (14.0 kcal/mol) obtained from the cluster model calculations by de Visser et al…”
Section: Resultssupporting
confidence: 90%
“…As such, the C–C bond cyclization is preferred over the hydroxylation. The calculated barrier exceeds the value of 12.5 kcal/mol reported in a QM-cluster model study . The comparison of structures showed that the substrate radical generated after hydrogen abstraction in the QM-cluster study lies 6.4 kcal/mol higher than that in our study (Figure S11).…”
Section: Resultscontrasting
confidence: 80%
See 3 more Smart Citations